Transformation of PAI Learning after The Covid-19 Pandemic - Surawan Surawan; Umiyati Wahidahtu Rohmah (Matan : Journal of Islam and Muslim Society, 2022)
PAI is a conscious effort made through a plan to prepare students to know, understand, Live their beliefs, and behave in accordance with the ethics, morals, and values prevailing in the society in accordance with the teachings of Islam. PAI learning during the covid-19 outbreak was conducted online using distance learning because PAI learning should have been practiced directly by students. Therefore, the effect of the pandemic makes students and educators close to the internet. Accessing the internet has an impact on students so most schools still prohibit the use of electronic goods such as smartphones or laptops in the school area. These rules certainly make students stressed and confident when they are in the school environment. For this reason, the purpose in this article is to find out the transformation of PAI after covid-19. The study in this article uses a literature study approach the results of this study show that PAI learning is transformed with media as a source of learning such as audio-visual media and print media and strategies that can be used are contextual teaching learning and blended learning strategies.